PENGARUH PEMBERIAN URINE KELINCI DENGAN KONSENTRASI YANG BERBEDA TERHADAP PERTUMBUHAN SETEK VANILI: - - Ariyanti, Mira; Suminar, Erni; Rosniawaty, Santi (Agrisaintifika: Jurnal Ilmu-ilmu Pertanian, 2023)
Vanilla plant propagation is usually done by cutting. Vanilla cuttings that are grown are expected to develop optimally into seeds which will eventually produce well. The thing that needs to be considered to support the growth of vanilla cuttings at a later stage is the adequacy of the supply of nutrients and growth determinants or PGR. Rabbit urine is a natural substance that contains certain nutrients and PGR which can be added to support the growth and development of vanilla cuttings. This experiment aims to examine the effect of rabbit urine on the growth of vanilla cuttings. The experiment was conducted at the Office of the Sindanglaya Plantation Seeding Center, Bandung, West Java from August to November 2022. The experimental method was experimental using a completely randomized design with treatment without rabbit urine and rabbit urine with concentrations of 5%, 10% 15%, 20% respectively. Each treatment was repeated five times. The experimental results showed that administration of 15% concentration of rabbit urine produced the best growth in the parameters of the number of roots, number of leaves and shoot length of vanilla cuttings up to the age of 14 WAP